ACCOUNTING TREATMENT OF A BAD-DEBT RECOVERY. - Ashley, C. A. (The Accounting Review, 1942)
Abstract If the reserve is established as a percentage of receivables it makes little difference how a bad-debt recovery is treated as a credit to the reserve account or as a credit to an income account. A balance sheet at the end of a period would not be affected by a choice in the method of treating a recovery during the period. To the extent that a recovery is credited to the reserve account during the period the usual addition to the reserve at the end of the period will be less. The final balances in the accounts for outstanding receivables and the reserve will not be affected by a choice in the method of recording recoveries. Furthermore, net profit would be the same in either case. In one case a larger bad debt expense would be exactly offset by the income of bad debt recoveries. If the reserve is on a budgetary basis, increased by a percentage of sales, the question of bow to treat a recovery becomes pertinent because the balance sheet and net profit will be affected by the decision. A credit to the reserve account is conservative but theoretically the answer to the question will depend on how the percentage was determined.